2007
DOI: 10.1097/id.0b013e31815c8ef4
|View full text |Cite
|
Sign up to set email alerts
|

Bone Block Allograft Impregnated With Bone Marrow Aspirate

Abstract: Impregnation of bone-marrow aspirate into allograft bone block activates the body's ability to form new bone. The bone-marrow aspiration technique is less invasive than harvesting autogenous bone from a second surgical site, offers predictable results, and is cost effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 49 publications
0
30
0
1
Order By: Relevance
“…), bone marrow derived mesenchymal stem cells (BMSCs) were the first described MSCs and remain among the most reliable and relevant sources of MSCs for skeletal regeneration (Friedenstein, Gorskaja, & Kulagina, 1976; Gronthos et al, 2003; Knight & Hankenson, 2013). For years, the iliac crest or long bones such as the tibia and femur have been most commonly utilized to obtain BMSCs for craniofacial regeneration (Cerruti et al, 2007; Kaigler et al, 2013; Kawaguchi et al, 2004; Li, Yan, Lei, Li, & Xiao, 2009; Marei, Nouh, Saad, & Ismail, 2005; Soltan, Smiler, Prasad, & Rohrer, 2007; Xie et al, 2010), but it remains uncertain whether BMSCs from craniofacial bones are more potent for this purpose. Several recent studies isolated BMSCs from the maxilla and mandible by rinsing bone fragments or by flushing cells through the extraction sockets, and compared their properties with those from long bones or iliac crest so far (Aghaloo et al, 2010; Akintoye et al, 2006; Dong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…), bone marrow derived mesenchymal stem cells (BMSCs) were the first described MSCs and remain among the most reliable and relevant sources of MSCs for skeletal regeneration (Friedenstein, Gorskaja, & Kulagina, 1976; Gronthos et al, 2003; Knight & Hankenson, 2013). For years, the iliac crest or long bones such as the tibia and femur have been most commonly utilized to obtain BMSCs for craniofacial regeneration (Cerruti et al, 2007; Kaigler et al, 2013; Kawaguchi et al, 2004; Li, Yan, Lei, Li, & Xiao, 2009; Marei, Nouh, Saad, & Ismail, 2005; Soltan, Smiler, Prasad, & Rohrer, 2007; Xie et al, 2010), but it remains uncertain whether BMSCs from craniofacial bones are more potent for this purpose. Several recent studies isolated BMSCs from the maxilla and mandible by rinsing bone fragments or by flushing cells through the extraction sockets, and compared their properties with those from long bones or iliac crest so far (Aghaloo et al, 2010; Akintoye et al, 2006; Dong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The application of non-absorbable barrier membranes had no significant effect on new bone formation. It has been reported that successful bone augmentation can be achieved using CHBB impregnated with bone marrow aspirate 19 . From these results, it is conceivable that CHBB with excellent activity of new bone formation and space maintenance in conjunction with collagen (which maintains and controls the release of rhBMP-2) can lead to a better outcome in wide vertical ridge augmentation.…”
mentioning
confidence: 99%
“…10 However, we must consider that when autogenous bone graft is used, bone resorption must be expected with no predictable percent bone loss.…”
Section: Discussionmentioning
confidence: 99%